Altered fire regimes cause long‐term lichen diversity losses. (8th August 2018) - Miller, Jesse E. D.; Root, Heather T.; Safford, Hugh D.
Abstract: Many global ecosystems have undergone shifts in fire regimes in recent decades, such as changes in fire size, frequency, and/or severity. Recent research shows that increases in fire size, frequency, and severity can lead to long‐persisting deforestation, but the consequences of shifting fire regimes for biodiversity of other vegetative organisms (such as understory plants, fungi, and lichens) remain poorly understood. Understanding lichen responses to wildfire is particularly important because lichens play crucial roles in nutrient cycling and supporting wildlife in many ecosystems. Lichen responses to fire have been little studied, and most previous research has been limited to small geographic areas (e.g. studies of a single fire), making it difficult to establish generalizable patterns. To investigate long‐term effects of fire severity on lichen communities, we sampled epiphytic lichen communities in 104 study plots across California's greater Sierra Nevada region in areas that burned in five wildfires, ranging from 4 to 16 years prior to sampling. The conifer forest ecosystems we studied have undergone a notable increase in fire severity in recent decades, and we sample across the full gradient of fire severity to infer how shifting fire regimes may influence landscape‐level biodiversity. We find that low‐severity fire has little to no effect on lichen communities. Areas that burned at moderate and high severities, however, have significantly and progressively lower lichen richness and abundance. Importantly, we observe very little postfire lichen recolonization on burned substrates even more than 15 years after fire. Our multivariate model suggests that the hotter, drier microclimates that occur after fire removes forest canopies may prevent lichen reestablishment, meaning that lichens are not likely to recolonize until mature trees regenerate. These findings suggest that altered fire regimes may cause broad and long‐persisting landscape‐scale biodiversity losses that could ultimately impact multiple trophic levels. Abstract : Lichens play crucial roles in nutrient cycling and supporting wildlife in many ecosystems, but their responses to disturbance are poorly understood. In this study, we find that shifts in disturbance regimes away from historical conditions (i.e. increases in fire severity) lead to sharp and long‐persisting reductions in lichen richness and abundance. In our study system, the hotter, drier microclimates that occur after stand‐replacing fires appear to hinder lichen reestablishment; these findings suggest that altered fire regimes may cause broad and long‐persisting landscape‐scale lichen diversity losses that could ultimately impact multiple trophic levels.